1997
DOI: 10.1037/0022-3514.72.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Emotional responses to goal attainment: Strength of regulatory focus as moderator.

E. Tory Higgins,
James Shah,
Ronald Friedman

Abstract: Goals with a promotion focus versus a prevention focus are distinguished. Chronic ideal goals (hopes and aspirations) have a promotion focus, whereas ought goals (duties and responsibilities) have a prevention focus. The hypothesis that emotional responses to goal attainment vary as a function of promotion versus prevention goal strength (conceptualized as goal accessibility) was tested in correlational studies relating chronic goal attainment (self-congruencies or self-discrepancies) to emotional frequency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
871
2
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 833 publications
(932 citation statements)
references
References 18 publications
(20 reference statements)
29
871
2
8
Order By: Relevance
“…With regard to affective pleasure and pain, successful attainment of nurturance-related goals within a promotion focus engenders cheerfulness-related affect, whereas failure within a promotion focus leads to dejection-related affect. In contrast, successful attainment of security-related goals within a prevention focus engenders quiescence-related affect, while failure within a prevention focus leads to agitationrelated affect (Higgins, Shah, & Friedman, 1997). Whereas the motivational orientation in a promotion focus, which is concerned with gains and non-gains, is eagerness, the motivational orientation in a prevention focus, which is concerned with losses and non losses, is vigilance (see for example, Förster, Higgins, & Taylor Bianco, in press).…”
Section: Discussionmentioning
confidence: 99%
“…With regard to affective pleasure and pain, successful attainment of nurturance-related goals within a promotion focus engenders cheerfulness-related affect, whereas failure within a promotion focus leads to dejection-related affect. In contrast, successful attainment of security-related goals within a prevention focus engenders quiescence-related affect, while failure within a prevention focus leads to agitationrelated affect (Higgins, Shah, & Friedman, 1997). Whereas the motivational orientation in a promotion focus, which is concerned with gains and non-gains, is eagerness, the motivational orientation in a prevention focus, which is concerned with losses and non losses, is vigilance (see for example, Förster, Higgins, & Taylor Bianco, in press).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, attainment of prevention goals may induce feelings of relief and quiescence and their non-attainment feelings of anxiety and agitation. In support of these ideas, Higgins and his colleagues found that framing the same activity (i.e., solving anagrams) as means to a promotion or a prevention goal led to the predicted, qualitatively different, emotional experiences of joy and of quiescence, respectively, upon pursuing the goal through the activity (Higgins, Shah, & Friedman, 1997). We further predict that the transfer of affective qualities from promotion and prevention goals will be proportionate to the strength of association between the goals and the means pursued in order to attain them.…”
Section: Quantitative and Qualitative Aspectsmentioning
confidence: 96%
“…Importantly, felt accountability is advanced as a psychological mechanism through which external societal constraints ultimately influences behavior (Propositions 3a,3b what a person believes is his or her responsibility to be, based either on prescriptions from close others or prescriptions from the generalized society, the latter of which is referred to as "normative ought-guides" (Higgins, 1996). Higgins, Shah, and Friedman (1997) showed that there are individual differences in the accessibility of ideal and ought self-guides. We predict that individuals in tight societies, who have higher felt accountability, will tend to have chronic accessibility of normative ought self-guides and a prevention regulatory focus (i.e., will be focused on not making mistakes).…”
Section: Means and Variancementioning
confidence: 99%